2019
DOI: 10.3390/jcm8081096
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Encapsulated Thymidine Phosphorylase for the Treatment of Patients with Mitochondrial Neurogastrointestinal Encephalomyopathy: Study Protocol for a Multi-Centre, Multiple Dose, Open Label Trial

Abstract: Mitochondrial neurogastrointestinal encephalomyopathy (MNGIE) is an autosomal recessive disorder which primarily affects the gastrointestinal and nervous systems. This disease is caused by mutations in the nuclear TYMP gene, which encodes for thymidine phosphorylase, an enzyme required for the normal metabolism of deoxynucleosides, thymidine, and deoxyuridine. The subsequent elevated systemic concentrations of deoxynucleosides lead to increased intracellular concentrations of their corresponding triphosphates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 32 publications
(44 reference statements)
0
35
0
Order By: Relevance
“…EryDel, in turn, focused on clinical trials of dexamethasone (EryDex) for the treatment of ataxia telangiestasia [245]. A device developed by EdyDel was also used to prepare thymidine phosphorylase in erythrocytes (EE-TP) for the treatment of mitochondrial neurogastrointestinal encephalomyopathy [246].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EryDel, in turn, focused on clinical trials of dexamethasone (EryDex) for the treatment of ataxia telangiestasia [245]. A device developed by EdyDel was also used to prepare thymidine phosphorylase in erythrocytes (EE-TP) for the treatment of mitochondrial neurogastrointestinal encephalomyopathy [246].…”
Section: Resultsmentioning
confidence: 99%
“…β-Galactosidase - [21] β-Glucocerebrosidase (β-glucosidase) Gaucher disease [21,37,38,[44][45][46]250] β-Glucuronidase Syndrome Slaya [251] l-Phenylalanine ammonia lyase Phenylketonuria [48,252,253] Phenylalanine hydroxylase [50,254] Uricase (uratoxidase) Uric acid removal [255,256] Urease, urease + alanine dehydrogenase Urea utilization [257][258][259] Adenosine deaminase Severe combined immunodeficiency caused by deaminase deficiency [27,[55][56][57][58]260] Thymidine phosphorylase Mitochondrial neurogastrointestinal encephalomyopathy (MNGIE) [56,246,261,262] Glutamate dehydrogenase Hyperammonemia [59,60,72] Glutamine synthetase [73,74] Glutamate dehydrogenase + alanine aminotransferase [11,63] Arginase Hyperammonemia due to arginase deficiency [263] Alcohol dehydrogenase…”
Section: Active Substance Application Referencesmentioning
confidence: 99%
“…Moreover, the variability of hyperlipaemic plasma was observed at 152.21%. Although hyperlipidaemia has been reported in some patients with MNGIE, the assay interference of lipids at this low concentration of 2'-deoxyuridine (equivalent to 0.12 µmol/L) will have no impact on the pharmacodynamic evaluation of EE-TP as the set criteria for metabolic correction in the clinical trial is a plasma 2'-deoxyuridine concentration 25 times higher than this, at <5 µmol/L (criteria for thymidine is a concentration <3 µmol/L) [14,21]. Thymidine: High QC = 7500 ng/mL, Low QC = 30 ng/mL; 2'deoxyuridine: High QC = 37.5 µg/mL, Low QC = 3 µg/mL.…”
Section: Recovery and Matrix Effectmentioning
confidence: 96%
“…One of the trial's primary objectives is the longitudinal assessment of the pharmacodynamic effects of EE-TP for optimizing dose level selection and establishing a therapeutic window for treatment. These pharmacodynamic assessments include the measurement of plasma and urine thymidine and 2'-deoxyuridine concentrations [14]. There is thus a requirement for validated bioanalytical methods in accordance with the regulatory guidelines for the quantification of thymidine and 2'-deoxyuridine in collected plasma and urine samples.…”
Section: Introductionmentioning
confidence: 99%
“…Regulations SI 1994/3144, where Schedule 1 provides an exemption from the need for a marketing authorisation for a relevant medicinal product, which is supplied on an individual patient basis to fulfil a "special need". In the early stage of development, the encapsulation of thymidine phosphorylase was performed using a manual process, but for the clinical trial, which has regulatory approval in the United Kingdom, an automated encapsulation process will be employed [98] . In the first proof of concept study, the administration of one dose of EE-TP (34 U/kg body weight) was reported to decrease the urinary excretion of thymidine and 2'-deoxyuridine at three days post infusion to 6% and 13%, respectively, of the amounts excreted pre-therapy.…”
Section: Ee-tpmentioning
confidence: 99%